A Pilot Study Evaluating the Safety of Intravenously Administered Human Amnion Epithelial Cells for the Treatment of Hepatic Fibrosis - Lim, Rebecca; Hodge, Alexander; Moore, Gregory; Wallace, Euan M.; Sievert, William (Frontiers in Pharmacology, 2017)
Liver cirrhosis is the 6th leading cause of death in adults aged 15 – 59 years in high-income countries. For many who progress to cirrhosis, the only prospect for survival is liver transplantation. While there is some indication that mesenchymal stem cells may be useful in reversing established liver fibrosis, there are limitations to their widespread use – namely their rarity, the need for extensive serial passaging and the associated potential for genomic instability and cellular senescence. To this end, we propose the use of allogeneic amnion epithelial cells. This clinical trial will assess the safety of intravenously delivered allogeneic hAECs in patients with compensated liver cirrhosis. This will also provide clinical data that will inform phase 2 and 3 clinical trials with the ultimate goal of developing hAECs as a therapeutic option for patients with cirrhosis who are at significant risk of disease progression. We will recruit 12 patients with compensated cirrhosis, based on their hepatic venous pressure gradient, for a dose escalation study. Patients will be closely monitored in the first 24 hours post-infusion, then via daily telephone interviews until clinical assessment on day 5. Long term follow up will include standard liver tests, transient elastography and hepatic ultrasound. Ethics approval was obtained from Monash Health for this trial 16052A, “A Pilot Study Evaluating the Safety of Intravenously Administered Human Amnion Epithelial Cells for the Treatment of Liver Fibrosis, A First in Adult Human Study”. The trial will be conducted in accordance to Monash Health Human Ethics guidelines. Outcomes from this study will be disseminated in the form of conference presentations and submission to a peer reviewed journal. This trial has been registered on the Australian and New Zealand Clinical Trials Registry ACTRN12616000437460.